Salient stakeholder identification for forestry-based ecotourism in Peninsular Malaysia - Yip, Hin Wai; Mohd, Abdullah; Wan Mohd, Wan Razali; Mariapan, Manohar; Abd. Ghani, Awang Noor (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Stakeholder engagement is widely adopted in managing inter-organizational relationships. Ecotourism management also adopts this approach to ensure the achieving of sustainable development by incorporating ecological and social perspectives. Therefore, in pursuing ecotourism, forest managers have to cater to different opinions and demands from various stakeholders besides protecting its own institutional interest. Demands by stakeholders have to be managed with a strategic management approach. The initial step is to identify salient stakeholders based on legitimacy, power and urgency claims. Conventional stakeholder identification is based solely on legitimacy claims of the stakeholders. Experiences from various stakeholder engagements have shown that stakeholder salience have included attributes of power and urgency. By using the strategic approach, potential stakeholders could be identified based on their inherent attributes, i.e. their interests or policies, which encompass issues related to forests or ecotourism, are included in the ecotourism management. In Malaysian forestry perspectives, besides the forestry department, several competing agencies also focus on ecotourism development in the forest settings where pursue of these agencies could neglect the main stakeholders‟ interests. Hence, as the main stakeholder in forestry, forestry departments could adopt this approach in identifying and later managing their stakeholders for ecotourism development. This paper identifies different categories of stakeholders and salient stakeholders using the three attributes.